Selective and Sensitive Fluorescence Turn‐On Detection of Cyanide Ions in Water by Post Metallization of a MOF. Issue 1 (13th December 2021) - Mahato, Debanjan; Fajal, Sahel; Samanta, Partha; Mandal, Writakshi; Ghosh, Sujit K.
Abstract: Owing to detrimental impact of cyanide ion (CN − ) towards the entire living system as well as its availability in drinking water, it has become very important developing potential sensory materials for the selective and sensitive recognition of CN − ions in water. In the domain of sensory materials, luminescent metal‐organic frameworks (LMOFs) have been considered as a promising candidate owing to their unique host‐guest interaction, where MOFs can serve as an ideal scaffold for encapsulating relevant guest molecules rendering specific functionality. In this study, a post‐synthetically modified MOF (viz., CuCl2 @MOF‐867) was applied to recognize cyanide (CN − ) ions in water via "turn‐on" response. The bipyridyl functionalities in MOF‐867 were used to perform post‐synthetic metalation to infiltrate CuCl2 inside porous architecture of the MOF. Moreover, a CuCl2 @MOF‐867 based probe demonstrated highly selective and sensitive aqueous phase recognition of CN − ions even in the presence of other interfering anions such as Br −, NO3 −, I −, SO4 2−, OAc −, SCN −, NO2 −, etc. The selective binding of CN − ions to the copper‐metal center has led to the generation of stable Cu(CN)2 species. This phenomenon has further resulted in a fluorescence turn‐on response. The aqueous phase cyanide detection by the rationally modified MOF system exhibited very low limit of detection (0.19 μM), which meets the standardized limit stated by World Health Organization (WHO) that is 1.9 μM. Abstract : A potential sensory material has been developed by post metallization of a metal‐organic framework, constructed with bipyridyl functionality as organic linker. The sensory probe demonstrates highly selective and sensitive aqueous phase "turn‐on" detection towards hazardous cyanide ions even in the presence of other interfering ions with a very low limit of detection (0.19 μM), considerably lower than the WHO permissible limit.